Feminism, interrupted : disrupting power - Olufemi, Lola (Outspoken (Pluto Press), 2020)
Plastered over t-shirts and tote bags, the word 'feminist' has entered the mainstream and is fast becoming a popular slogan for our generation. But feminism isn't a commodity up for purchase; it's a weapon for fighting against injustice. This revolutionary book reclaims feminism from consumerism through exploring state violence against women, reproductive justice, transmisogyny, sex work, gendered Islamophobia and much more, showing that the struggle for gendered liberation is a struggle for justice, one that can transform the world for everyone.